Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry as a useful tool for the rapid identification of wild flea vectors preserved in alcohol. Issue 2 (5th December 2018) - Zurita, A.; Djeghar, R.; Callejón, R.; Cutillas, C.; Parola, P.; Laroche, M.
Abstract: Flea identification is a significant issue because some species are considered as important vectors of several human pathogens that have emerged or re‐emerged recently, such as Bartonella henselae (Rhizobiales: Bartonellaceae) and Rickettsia felis (Rickettsiales: Rickettsiaceae). Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) has been evaluated in recent years for the identification of multicellular organisms, including arthropods. A preliminary study corroborated the usefulness of this technique for the rapid identification of fleas, creating a preliminary database containing the spectra of five species of flea. However, longterm flea preservation in ethanol did not appear to be an adequate method of storage in the context of specimen identification by MALDI‐TOF MS profiling. The goal of the present work was to assess the performance of MALDI‐TOF MS in the identification of seven flea species [ Ctenocephalides felis (Siphonaptera: Pulicidae), Ctenocephalides canis, Pulex irritans (Siphonaptera: Pulicidae), Archaeopsylla erinacei (Siphonaptera: Pulicidae), Leptopsylla taschenbergi (Siphonaptera: Ceratophyllidae), Stenoponia tripectinata (Siphonaptera: Stenoponiidae) and Nosopsyllus fasciatus (Siphonaptera: Ceratophyllidae)] collected in the field and stored in ethanol for different periods of time. The results confirmed that MALDI‐TOF MS can be used for the identification of wild fleas stored in ethanol. Furthermore, this technique was able to discriminate not only different flea genera, but also the two congeneric species C. felis and C. canis . Abstract : MALDI‐TOF MS was able to identify seven fleas preserved in alcohol. This protocol is valid for various ethanol concentrations and prevents the impact of host blood on identification. This approach was able to discriminate congeneric flea species.